One perfect lie - Scottoline, Lisa; Newbern, George, 1964- (New York, NY : Macmillan Audio, 2017)
When her son is recruited by a Division I school, a struggling single mom's efforts are complicated by her son's teammate who is luring him down a dark path and a new teacher with a mysterious agenda.
Read by George Newbern.
Keywords: Single parents -- Fiction; Impostors and imposture -- Fiction; Suspense fiction; Audiobooks